PEMBUATAN BAHAN BAKAR CAIR DARI TREMBOSO (SISA SADAPAN LATEKS) MENGGUNAKAN KATALIS ZEOLIT MODERNITE - Dian Cahyaningrum; Nerfiana Fradevi; Didi Dwi Anggoro (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Modernite very well used as an acid catalyst for the cracking process, to get a good acid levels can be modified catalyst by dealumination process. Dealumination will provide a ratio of Si / Al higher which can provide the catalyst selectivity and activity of catalysts are higher and more stable than modernite the ratio of Si / Al 20. In this study, using raw materials such as used cooking oil and zeolite catalysts modernite types. In an influential study variable, didapaatkan equations for liquid products is Y = -120.858 + 4.869 + 1.473 X1 + X2 + X3 59.183 0.043 X1X2 - X1X3 0.733 - 0.320 X2X3 - X1 0.324 2 to 0.008 X22 - X32 6.075. As for the product gas mathematical equation is Y = 122.3022 + 1.5447 X1 - 0.8713 X2 + X3 + 55.8804 0.0357 X1X2 - 0.8281 X1X3 - X2X3 0.0547 - 0.0643 X12 + 0, 10.7038 + 0076 X22 X32, the Y is the yield resulting product, X1 is a dealumination, X2 is the operating temperature, and X3 is the concentration. Optimal conditions maximizing the type contained in the concentration versus time relationship, with a time of 8 hours and a concentration dealumination 3 N for liquid products, while for the product gas at 8 hours with an operating temperature of 50 ° C.